2021
DOI: 10.3389/fcell.2021.628317
|View full text |Cite
|
Sign up to set email alerts
|

PFKFB3: A Potential Key to Ocular Angiogenesis

Abstract: The current treatment for ocular pathological angiogenesis mainly focuses on anti-VEGF signals. This treatment has been confirmed as effective despite the unfavorable side effects and unsatisfactory efficiency. Recently, endothelial cell metabolism, especially glycolysis, has been attracting attention as a potential treatment by an increasing number of researchers. Emerging evidence has shown that regulation of endothelial glycolysis can influence vessel sprouting. This new evidence has raised the potential fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 138 publications
0
9
0
Order By: Relevance
“…PFKFB3-driven glycolysis has been well documented in endothelial pathophysiology, including valve formation, vessel sprouting, etc. 40 42 We demonstrate that SAC reverses PFKFB3 induction by promoting its degradation and therefore limits augmented glycolysis and EndoMT. Specific PFKFB3 kinase inhibitors PFK-015, 3PO, and endothelial Pfkfb3 haplodeficiency conformably recapitulate the effects of SAC in suppression of EndoMT in vitro and in vivo, further supporting this rationale.…”
Section: Discussionmentioning
confidence: 79%
“…PFKFB3-driven glycolysis has been well documented in endothelial pathophysiology, including valve formation, vessel sprouting, etc. 40 42 We demonstrate that SAC reverses PFKFB3 induction by promoting its degradation and therefore limits augmented glycolysis and EndoMT. Specific PFKFB3 kinase inhibitors PFK-015, 3PO, and endothelial Pfkfb3 haplodeficiency conformably recapitulate the effects of SAC in suppression of EndoMT in vitro and in vivo, further supporting this rationale.…”
Section: Discussionmentioning
confidence: 79%
“…PFKFB3 has been shown to be widely expressed in different tissues and organs and to play an important role in regulating angiogenesis [ 23 , 24 ]. Therefore, we hypothesized that the targeted delivery of PFKFB3 to the placenta would promote angiogenesis and thus enhance placental function, and that an increased placental weight would lead to a corresponding increase in fetal weight.…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, PFKFB3, a key regulator of glycolysis, has been shown to play an increasingly important role in regulating angiogenesis through metabolic pathways independent of genetic signals [ 14 , 24 ]. De Bock et al [ 10 ] showed that PFKFB3-mediated glycolysis could directly regulate vascular sprouting and promote angiogenesis, and that inactivation of the PFKFB3 gene could inhibit angiogenesis in mice [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…In renal cell carcinoma, PFKFB3 knockout inhibits glycolysis and cell proliferation, suggesting that PFKFB3 could be used as a potential therapeutic target ( 83 ). Emerging evidence has shown that PFKFB3 also plays an important role in regulating physiological and pathological angiogenesis ( 84 ). Endothelial proliferation depends on glycolysis: 85% of ATP is produced by converting glucose into lactate, and pharmacological inhibition of PFKFB3 damages the development of the mouse retinal vascular system ( 85 ).…”
Section: The Regulatory Mechanism Of Hif-1α In Renal Fibrosismentioning
confidence: 99%